Cross-reactive antibodies against Langat virus protect mice from lethal tick-borne encephalitis virus infection - Kubinski, Mareike; Beicht, Jana; Zdora, Isabel; Saletti, Giulietta; Kircher, Magdalena; Petry-Gusmag, Monique; Steffen, Imke; Puff, Christina; Jung, Klaus; Baumgärtner, Wolfgang; Rimmelzwaan, Guus F.; Osterhaus, Albert D. M. E.; et al. (Frontiers in Immunology, 2023)
Naturally attenuated Langat virus (LGTV) and highly pathogenic tick-borne encephalitis virus (TBEV) share antigenically similar viral proteins and are grouped together in the same flavivirus serocomplex. In the early 1970s, this has encouraged the usage of LGTV as a potential live attenuated vaccine against tick-borne encephalitis (TBE) until cases of encephalitis were reported among vaccinees. Previously, we have shown in a mouse model that immunity induced against LGTV protects mice against lethal TBEV challenge infection. However, the immune correlates of this protection have not been studied. In the present study, we showed that mouse infection with LGTV induced both cross-reactive antibodies and T cells against TBEV. To identify correlates of protection, we performed adoptive transfer of either serum or T cells from LGTV infected mice into naïve recipient mice and challenged them with lethal dose of TBEV. Monitoring the disease progression in these mice for 16 days post infection, showed that serum from LGTV infected mice efficiently protected from developing severe disease. On the other hand, adoptive transfer of T cells from LGTV infected mice failed to provide protection. Histopathological investigation of infected brains suggested a possible role of microglia and T cells in inflammatory processes within the brain. Our data provide key information regarding the immune correlates of protection induced by LGTV infection of mice which may help design better vaccines against TBEV.